2021
DOI: 10.1037/pag0000531
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the influence of temporal factors on age differences in working memory dual task costs.

Abstract: Working memory is defined by many as the system that allows us to simultaneously store information over brief time periods while engaging in other information processing activities. In a previous study (Rhodes, Jaroslawska et al. (2019) Journal of Experimental Psychology: General, 148, 1204-1227 we found that retention of serially presented letters was disrupted by the introduction of an arithmetic processing task during a 10 second delay period. Importantly, the magnitude of this dual task disruption increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 77 publications
(128 reference statements)
0
4
0
Order By: Relevance
“…The collaboration was therefore concerned with examining dual-task effects under very controlled conditions (such as equating the storage and processing tasks for difficulty across individuals before combining them into a dual task). The results established the presence of some dual-task effects and not others and was of tremendous value in creating test conditions that both groups could trust (Belletier et al, in press;Doherty et al, 2019;Jaroslawska et al, 2021;Rhodes et al, 2021;Rhodes, Jaroslawska, et al, 2019). It was not, however, well suited for a broad-ranging spectrum of research that would be needed to settle the fundamental issue of the role of attention in working memory.…”
Section: The Kinds Of Issues Best Suited To Adversarial Collaborationmentioning
confidence: 96%
“…The collaboration was therefore concerned with examining dual-task effects under very controlled conditions (such as equating the storage and processing tasks for difficulty across individuals before combining them into a dual task). The results established the presence of some dual-task effects and not others and was of tremendous value in creating test conditions that both groups could trust (Belletier et al, in press;Doherty et al, 2019;Jaroslawska et al, 2021;Rhodes et al, 2021;Rhodes, Jaroslawska, et al, 2019). It was not, however, well suited for a broad-ranging spectrum of research that would be needed to settle the fundamental issue of the role of attention in working memory.…”
Section: The Kinds Of Issues Best Suited To Adversarial Collaborationmentioning
confidence: 96%
“…Importantly, task demands were adjusted beforehand to ensure age differences did not reflect baseline disparities in single-task performance [75]. Notably, age-related differences in working memory dual-tasking are not attributed to encoding speed limitations [76]. Verhaeghen and Zhang (2013) tested younger and older adults with a modified version of the N-back task.…”
Section: Plos Onementioning
confidence: 99%
“…The details of these experiments have been reported elsewhere (e.g., Doherty et al, 2019 ; Jaroslawska et al, 2021 ; Rhodes et al, 2019 , 2021 ; for a comprehensive list see http://womaac.psy.ed.ac.uk/research-output ). As an illustration, Figure 10 shows the predictions from each theoretical perspective for one of the experiments reported in Doherty et al (2019) along with the observed results.…”
Section: An Extended Adversarial Collaboration: the Womaac Projectmentioning
confidence: 99%